Pedro Páramo, A Metaphor for the End of the World - Julio Ortega (Studies in 20th & 21st Century Literature, 1990)
In Rulfo's novel, popular Catholic culture functions as an ideology and as such, it encompasses the totality of the represented universe. Because reality is only captured through ideology, there is no criterion in the novel that is outside ideology and which would therefore offer a critical standpoint, though this criterion does exist by implication in the world of the reader.
Keywords: Pedro Páramo; Juan Rulfo; Catholicism; ideology; totalism